Current status and influencing factors of different initiation time of antiretroviral therapy in HIV/AIDS patients - GUAN Yuan; DING Yingying; LU Hongzhou (Shanghai yufang yixue, 2023)
ObjectiveTo investigate the status of different antiretroviral therapy（ART） initiation times in patients with HIV/AIDS and analyze the relevant characteristics and influencing factors of delayed ART.MethodsFrom December 2018 to December 2020， a survey was conducted among adult HIV/AIDS patients treated in 28 designated AIDS prevention and treatment institutions in Beijing， Shanghai， Guangdong， Jiangsu， Henan， Jiangxi， Guangxi， Yunnan and other places. Data of the basic demographic information， lifestyle and chronic disease prevalence， and characteristics of diagnosis and treatment were collected. The characteristics and related factors of delayed ART were compared and analyzed.ResultsThe median age of 1 741 patients was 41 years old （IQR： 32‒52）. The initial CD4 count of most patients was less than 200 cells·μL-1（51.4%）. Among them， 1 027 patients had delayed ART （59.0%）， and the association between ART initiation time and initial CD4 count varied with the time of diagnosis of HIV infection. Multivariate logistic analysis showed that the older age （aOR=0.99， 95%CI： 0.98‒0.99） was associated with a higher rate of starting ART within 1 month after diagnosis， while those diagnosed before 2017 and with the initial CD4 count >200 cells·μL-1 were more likely to delay ART. Delayed initiation of ART may be a risk factor for poor sleep quality and co-infection in HIV/AIDS patients.ConclusionWith the expansion of free ART in China， the proportion of delayed ART with HIV/AIDS shows a downward trend. Timely ART management should be strengthened for the young HIV/AIDS patients and patients with high CD4 counts.